The importance of club activities for mentally retarded children in the Philippines - Dalope, Nieves A. 1938-; Valdes, Matilde M. (1967)
This study identifies club activities of the mentally retarded children in the Philippines and the benefits they derive from these activities.
Thesis (Master of Arts in Teaching - Special Education : Mental Retardation)--University of the Philippines, Diliman.
Keywords: Clubs; Mentally handicapped children -- Philippines